The impact of the European Medicines Agency (EMA) and the Heads of Medicines Agencies (HMA) to address shortages of human and veterinary medicines across Europe - Abed, Inga; Bennett, Vanessa; Cuddy, Brendan; Dang, Sandra; García Burgos, Juan; Di Giorgio, Domenico; Lamas, Maria; Radulovic, Momir; Simões, Nuno; Santos Ivo, Rui; Malonne, Hugues; Dias, Monica (Frontiers in Public Health, 2025)
Shortages of medicines are a global public health challenge with a significant impact on patient care. While the issue is at the top of the agenda of EU policymakers, regulators and healthcare providers, shortages are a complex problem with many contributing factors requiring multifaceted solutions. This article is a reflection of the work EMA and network of EU regulatory agencies for medicines carried out since 2012, in particular its taskforce, set up in 2016 to provide strategic and structural solutions to tackle shortages in the EU. Since its inception, the taskforce played a key role in spearheading activities related to medicines’ shortages. Members of the taskforce supported important initiatives from leading the work on critical medicines to laying the foundation for Regulation (EU) 2022/123, which reinforces EMA’s role in crisis preparedness and management of medicinal products and medical devices. On 18 December 2024 the taskforce reached the end of its mandate. Its work is now integrated into EMA and HMA’s core activities. Future activities such as the implementation of shortage prevention plans will be further defined by measures in the revised pharmaceutical legislation, and the proposed Critical Medicines Act.